Micro-Computed Tomography Reveals a Remarkable Twin Intromittent Organ in Spiders – A Novelty for Arachnids With Direct Sperm Transfer - Rix, Michael G.; Wood, Hannah M.; Harvey, Mark S.; Michalik, Peter (Frontiers in Ecology and Evolution, 2021)
The modification of male pedipalps into secondary sexual intromittent organs is one of the hallmark characteristics of spiders, yet understanding the development and evolution of male genitalia across the order remains a challenging prospect. The embolus – the sclerite bearing the efferent spermatic duct or spermophor, and used to deliver sperm directly to the female genitalia during copulation – has always been considered the single unambiguously homologous palpal sclerite shared by all spider species, fundamental to the bauplan of the order and to the evolution and functional morphology of spider reproductive systems. Indeed, after two centuries of comparative research on spider reproduction, the presence of a single spermophor and embolus on each of a male spider’s two pedipalps remains a central tenet of evolutionary arachnology. Our findings challenge this premise, and reveal a remarkable twin intromittent organ sperm transfer system in a lineage of Australian palpimanoid spiders, characterised by a bifurcate spermophor and the presence of two efferent ducts leading to a pair of embolic sclerites on each pedipalp. This is the first time such a remarkable conformation has been observed in any group of arachnids with direct sperm transfer, complicating our understanding of palpal sclerite homologies, and challenging ideas about the evolution of spider genitalia.